The Process Play and Life Wondrous - Bishop, J. K. (Canadian Journal of Counselling and Psychotherapy, 2011)
In this paper the wonders of life are explored as functions of children and parents in change. Presented are examples of cases in progress. Hinting at theory play means change. These create new means and methods in a new world. Hope endures.